Frequency of CSF Leak after Primary Repair of Incidental Durotomy in Lumbar Spine Surgery with use of Fibrin Glue - Ahmed Sultan, Farhan Fateh Jang, Amna Malik (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find the frequency of CSF leakage after primary repair of incidental durotomy in lumbar spine surgery with use of fibrin glue. Study Design: Descriptive case series. Place and duration of study: Neurosurgery Unit 2, Punjab Institute of Neurosciences, Lahore General Hospital, Lahore from 25-02-2021 to 25-08-2021. Methodology: Sixty five patients admitted for lumbar spine surgery and informed written consent was taken. All the cases were operated in elective operation theatre. Valsalva maneuver was performed per-operatively in all patients to assess CSF leakage. In all patients having incidental durotomy diagnosed per-operatively, primary repair with Prolene 4-0 was done and sealed with fribrin glue. Patients were examined on daily basis for CSF leakage. In case of no complication, patient was discharged on day 07 after surgery. In case of CSF leakage on clinical examination, MRI spine was done. After discharge, patient was followed in OPD on weekly basis for 30 days. CSF leak was done as per operational definition. Results: Total of 65 patients, 41(63.1%) were in age group of 16-40 years and 187(36.9%) were in age group of 41-75 years and mean age was calculated as 38.93±11.47 years. There were 44(67.7%) were male whereas 21(32.2%) were females. Frequency of CSF leakage was 9(13.8%) after primary repair of incidental durotomy in lumbar spine surgery with use of fibrin glue. Practical Implication: We found that frequency of CSF leakage was 13.8% after primary repair of incidental durotomy in lumbar spine surgery with use of fibrin glue. The rate of CSF leakage is low. Therefore, we concluded that fibrin glue is useful for the treatment of incidental durotomy in lumber spine surgery. Conclusion: This study showed that the CSF leakage was 13.8%. As the rate of CSF leakage is low. Therefore, we concluded that fibrin glue is useful for the treatment of incidental durotomy in lumbar spine surgery. Keywords: Cerebrospinal Fluid Leak, Incidental Durotomy, Lumbar Spine Surgery.